Nutritive value of four by-product meals as potential protein sources in diets for Octopus maya - Méndez Aguilar, Francisco Daniel; Olvera Novoa, Miguel Ángel; Rodríguez Morales, Sergio; Rosas Vázquez, Carlos (HIDROBIOLÓGICA, 2016)
The nutritional value of four meals made from animal by-products of squid (SBM), tuna (TBM), poultry (PBM) and pork (POBM), and their potential use in diets for Octopus maya were evaluated. Lyophilized crab-meat meal (CRM) (Callinectes sapidus) was used as a reference for the nutritional requirements of the octopus. CRM had the highest crude protein (CP) content (847.2 g kg?1) and the lowest lipid content (27.5 g kg?1). SBM and PBM had more than 700 g kg?1 CP content, while TBM and POBM had less than 600 g kg?1. Lipid content varied between 75.3 (SBM) and 127.2 (PBM) g kg?1. Energy content of CRM was 17.5 MJ kg?1, and the maximum difference with respect to the by-product meals did not exceed 3 MJ kg?1. Amino acid analysis showed that SBM and PBM had high content of Thr, Ser and Ala, which are the most important amino acids for the metabolism of O. maya. Fatty acid analysis showed that they also had a high content of PUFA. PBM showed deficiencies in EPA and DHA content, but had a high content of linoleic acid, which can be a precursor of C:20 and C:22. Based on this, SBM and PBM have nutritional qualities which could be adequate for use as primary protein sources in artificial diets for O. maya.